Аналіз сучасних середовищ розробки програмного забезпечення - Білоус, М. Ю. (ХНУРЕ, 2020)
The work discusses modern development environments such as Microsoft Visual Studio. NetBeans, PyCharm. Based on analysis, main disadvantages and advantages of these popular integrated development environments are identified. Such an overview of modern systems is necessary for further research in field of user interface development.
Keywords: середовище розробки; мови програмування; програмне забезпечення; бібліотека